Analisis Pengaruh Aset Tetap, Likuiditas, Ukuran, dan Profitabilitas terhadap Struktur Kapital Perusahaan - Munawar, Aang (Jurnal Ilmiah Ranggagading (JIR), 2009)
This research is intended to examine empirically (empirically study) on factors influencing capital structure. Firmâs capital structure will influence firmâs value, with the result that test of factors influencing are very significant. Regression model utilized at this research is ordinary least square (OLS). Independent variable used at this research embraces 4 (four) variables, namely: (1) fixed assets, (2) solvency, (3) size of firmâs, (4) profitability. The test shows that the four independent variables have significant influence in different inclination with positive implication on capital structure theory development. Keywords: Empirical study; Capital Structure; Regression Model; Ordinary Least Square (OLS); Fixed Assets; Solvency; Size; profitability.